Customer Relationship Management Sistem Untuk Optimalisasi Sistem Rantai Pasok Pada Usaha Tambak Perikanan - Sahrul, Muh; Assidiq, Muhammad; Qashlim, Akhmad (UI DDI AGH AD Polewali Mandar, 2025)
This research aims to develop and implement a Customer Relationship Management (CRM) system to optimize the supply chain system in fish farming businesses. CRM systems are designed to increase operational efficiency, strengthen customer relationships, and optimize the flow of information throughout the supply chain. In the context of fish farming businesses, CRM can help in monitoring market needs, real-time stock management, and improving customer service through more effective communication. The research results show that implementing a CRM system is able to reduce operational costs, increase customer satisfaction, and strengthen the competitiveness of fish farming businesses in an increasingly competitive market. Through the integration of information technology, the CRM system provides a comprehensive solution to overcome challenges in supply chain management, while supporting the sustainability and growth of fisheries businesses.